Potential of Cellular Therapy for ALS: Current Strategies and Future Prospects - Lin, Ting-Jung; Cheng, Kuang-Chao; Wu, Luo-Yun; Lai, Wei-Yu; Ling, Thai-Yen; Kuo, Yung-Che; Huang, Yen-Hua (Frontiers in Cell and Developmental Biology, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive upper and lower motor neuron (MN) degeneration with unclear pathology. The worldwide prevalence of ALS is approximately 4.42 per 100,000 populations, and death occurs within 3 to 5 years after diagnosis. However, no effective therapeutic modality for ALS is currently available. In recent years, cellular therapy has shown considerable therapeutic potential because it exerts immunomodulatory effects and protects the MN circuit. However, the safety and efficacy of cellular therapy in ALS are still under debate. In this review, we summarize the current progress in cellular therapy for ALS. The underlying mechanism, current clinical trials, and the pros and cons of cellular therapy using different types of cell are discussed. In addition, clinical studies of mesenchymal stem cells (MSCs) in ALS are highlighted. The summarized findings of this review can facilitate the future clinical application of precision medicine using cellular therapy in ALS.